Method for manufacturing molded body for sheet electrode
By forming a first film containing the electrode active material and an electrolyte on the support, and flattening the second powder material thereon, the problem of uneven solid content concentration in the in-plane direction of the electrode material film in the prior art is solved, and a single-layer structure electrode material film with high concentration and uniformity is achieved.
Patent Information
- Application Number
- CN202380056129.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-28
- Filing Date
- 2023-07-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, it is difficult to produce a sheet-shaped electrode molded body for a single-layer structure with a high solid component concentration and a non-uniform solid component concentration in the in-plane direction on the support.
The first film is formed by applying the first material including the electrode active material and the electrolyte to the support, and a second powder material including the electrode active material but without the liquid component is applied to the first film, and an electrode material film with a single layer structure is formed. The second powder material is imparted using molded parts such as scrapers or rollers, and the thickness of the laminate is limited to promote mixing and uniformity.
The uniformity of the concentration of solid components in the in-plane direction is achieved, the adhesion and molding quality of the electrode material film are improved, and a sheet-shaped electrode molded body with a single-layer structure with a high solid component concentration and uniform solid components are formed.
Smart Images

Figure CN119604987A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a formed body for a sheet-like electrode. Background Art
[0002] In recent years, the development of semi-solid-state batteries has been explored.
[0003] The electrode used for the semi-solid battery is produced using, for example, an electrode material containing at least a powdered electrode active material and an electrolyte.
[0004] For example, a method is disclosed in Japanese Patent Gazette No. 2017-183079, wherein, after a first active material layer is formed by applying a first active material layer forming paste to a current collector, a second active material layer forming paste having a higher solid content than the first active material layer forming paste is applied to the first active material layer to form a second active material layer, thereby forming an electrode having a structure in which an active material layer including the first active material layer and the second active material layer is maintained on the current collector.
[0005] In addition, Japanese Patent Gazette No. 2018-147807 discloses a method for manufacturing an electrode for a secondary battery, which includes the following steps: forming a first layer by shaping first wet particles having a first solid content ratio into a film, forming a second layer by shaping second wet particles having a second solid content ratio higher than the first solid content ratio into a film, and supplying the first layer, the second layer, and a current collector to a roller gap between a pair of rotating rollers to form an electrode mixture layer in which the second layer and the first layer are sequentially stacked on the surface of the current collector. Summary of the invention
[0006] Technical issues to be solved by the invention
[0007] As an electrode used in a semi-solid battery, it is preferable to apply a technique for improving energy density by using a sheet-shaped electrode molded body having a single-layer structure containing a solid component such as an electrode active material at a higher concentration than an electrolyte.
[0008] In order to obtain a sheet-like electrode formed body containing solid components such as electrode active materials at high concentrations, an electrode material containing solid components such as electrode active materials at high concentrations compared to an electrolyte is sometimes used to form a method for an electrode material film of a single-layer structure on a support. However, it is difficult for an electrode material containing solid components at high concentrations to mix the electrolyte and the solid components into a uniform state, and sometimes an uneven solid component concentration is produced in the obtained electrode material film in the in-plane direction. Moreover, even in the case where an electrode material containing solid components such as electrode active materials at high concentrations compared to an electrolyte can be mixed into a uniform state, the electrode material has little adhesion to the support, and it is difficult to form an electrode material film on the support.
[0009] Therefore, the present invention has been completed in view of the above circumstances.
[0010] An object of one embodiment of the present invention is to provide a method for producing a sheet-shaped electrode molded body capable of producing a single-layer structure sheet-shaped electrode molded body having a high solid content concentration and little unevenness in the solid content concentration in the in-plane direction on a support.
[0011] Means for solving technical problems
[0012] The present invention includes the following aspects.
[0013] <1> A method for producing a sheet-shaped electrode molded body, comprising:
[0014] A first step is to provide a first material including an electrode active material and an electrolyte solution on a support to form a first film based on the first material; and
[0015] In the second step, a second powder material containing an electrode active material and no liquid component is provided on the first film.
[0016] Then, an electrode material film having a single-layer structure as a mixture of the first film and the second powder material is formed.
[0017] <2> The method for producing a sheet-shaped electrode molded body according to <1>, wherein:
[0018] The second step is a step in which, after applying a second powder material containing an electrode active material and no liquid component to the first film, the second powder material applied to the first film is flattened by a molding component and the thickness of the stack of the first film and the second powder material is limited.
[0019] <3> The method for producing a sheet-shaped electrode molded body according to <2>, wherein:
[0020] The forming part is a scraper or a roller.
[0021] <4> The method for producing a sheet-shaped electrode molded body according to <2>, wherein:
[0022] In the second step, the second powder material applied onto the first film is leveled by a vibrating scraper or roller.
[0023] <5> The method for producing a sheet-shaped electrode molded body according to <1>, wherein:
[0024] The second step is the following step: after imparting a second powder material containing an electrode active substance and not containing a liquid component to the first film, a film is placed on the second powder material imparted to the first film, and the second powder material is pressed from the film through a molding component, thereby flattening the second powder material imparted to the first film and limiting the thickness of the stack of the first film and the second powder material.
[0025] <6> A method for manufacturing a sheet electrode forming body according to any one of <2> to <5>, further comprising a third step, wherein after the second powder material applied to the first film is leveled in the second step and the thickness of the stack of the first film and the second powder material is limited, in the third step, the stack with limited thickness is compressed by a vibrating pressure component.
[0026] <7> The method for producing a sheet-like electrode molded body according to any one of <1> to <6>, wherein:
[0027] The solid content concentration of the first material is 5 volume % to 48 volume %.
[0028] <8> The method for producing a sheet-like electrode molded body according to any one of <1> to <7>, wherein:
[0029] The thickness of the electrode material film of the single-layer structure is 50 μm to 250 μm, and the solid content concentration is 50 volume % to 80 volume %.
[0030] Effects of the Invention
[0031] According to one embodiment of the present invention, a method for producing a sheet-shaped electrode molded body capable of producing a single-layer structure sheet-shaped electrode molded body having a high solid content concentration and little unevenness in the solid content concentration in the in-plane direction on a support body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic cross-sectional view for explaining the first step and the second step in the method for producing the electrode molded body according to the present invention.
[0033] Figure 2 This is a schematic cross-sectional view for explaining the manner in which the second powder material applied to the first film is flattened by the molding member in the second step.
[0034] Figure 3 This is a schematic cross-sectional view for explaining the manner in which the second powder material applied to the first film is flattened by the molding member in the second step.
[0035] Figure 4 This is a schematic cross-sectional view for explaining the step of pressurizing a single-layer electrode material film. DETAILED DESCRIPTION
[0036] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. Constituent elements represented by the same symbols in the drawings refer to the same constituent elements. The description of the constituent elements and symbols repeated in the drawings may sometimes be omitted. The ratio of the dimensions in the drawings does not necessarily represent the ratio of the actual dimensions.
[0037] In the present invention, the numerical range represented by "to" refers to a range including the numerical values recorded before and after "to" as the lower limit and the upper limit. In the numerical range recorded in stages in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment.
[0038] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0039] In the present invention, "(meth)acrylic acid" means both or either one of acrylic acid and methacrylic acid.
[0040] In the present invention, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.
[0041] In the present invention, a combination of two or more preferred aspects or configurations is a more preferred aspect or configuration.
[0042] In the present invention, the "solid content" refers to a component that is solid at 25°C and 1 atmosphere, and the "liquid content" refers to a component that is liquid at 25°C and 1 atmosphere.
[0043] In the present invention, the "width" of the support refers to the length in the direction perpendicular to the longitudinal direction. In the case of a long support, it refers to the length in the direction perpendicular to the longitudinal direction.
[0044] Furthermore, the "width direction" of the film forming member (e.g., scraper) refers to a direction orthogonal to the direction in which the film forming member moves relative to the surface of the support (i.e., the direction in which the electrode material film is formed on the support). In other words, the "width direction" of the scraper is sometimes also equivalent to the "width direction" of the electrode material film.
[0045] <Method for producing a molded body for sheet-shaped electrode>
[0046] The method for manufacturing a sheet-like electrode forming body involved in the present invention comprises: a first step of imparting a first material containing an electrode active substance and an electrolyte solution on a support to form a first film based on the first material; and a second step of imparting a second powder material containing an electrode active substance and no liquid component on the first film, and forming an electrode material film having a single-layer structure which is a mixture of the first film and the second powder material.
[0047] Hereinafter, the "sheet-shaped molded body for electrode" is also simply referred to as "molded body for electrode".
[0048] Furthermore, in the present invention, "electrode material film having a single-layer structure" means that there is no interface in the electrode material film.
[0049] In addition, as to whether a single-layer structure electrode material film is obtained by the manufacturing method of the electrode molding body involved in the present invention, it is confirmed, for example, by the following method. First, an electrode material with a desired high solid content concentration (for example, 70% by volume) is prepared in advance, and the electrode material, a pressing mold and a pressing frame are used to make a single-layer structure electrode material film of about 3 cm × 2 cm in size. The mass and thickness of the obtained electrode material film are measured, and it is used as a benchmark for the electrode material film with a solid content concentration of 70% by volume. Next, in the manufacturing method of the electrode molding body involved in the present invention, an electrode material film with a solid content concentration of 70% by volume is formed, and the thickness and mass of the obtained electrode material film are measured. If the measured value has the same tendency as the above-mentioned benchmark, it can be inferred that it is a single-layer structure electrode material film. In addition, by using a soft X-ray inspection device, the density of the electrode material film in the thickness direction can be measured. The measured density has no difference or abnormality in the thickness direction (such as abnormalities such as large voids), thereby confirming that it is a single-layer structure electrode material film.
[0050] In the present invention, the electrode material film of the single-layer structure preferably has a thickness of 50 μm to 250 μm and a solid content concentration of 50 volume % to 80 volume %. That is, the method for producing an electrode molded body according to the present invention preferably forms an electrode material film of the single-layer structure having a thickness of 50 μm to 250 μm and a solid content concentration of 50 volume % to 80 volume %.
[0051] In the present invention, “high solid content concentration” means that the solid content concentration is 50% by volume or more.
[0052] Here, the thickness of the electrode material film of the single-layer structure is defined as the arithmetic mean of thicknesses at three locations measured by cross-sectional observation. A known microscope (eg, a scanning electron microscope) can be used for cross-sectional observation.
[0053] The solid content concentration of the electrode material film is calculated based on the composition ratio of each component included in the electrode material film and the specific gravity of these components.
[0054] As described above, when a single-layer electrode material film is formed on a support using an electrode material containing a high concentration of solid components, the obtained electrode material film may have uneven solid component concentration in the in-plane direction.
[0055] Therefore, the inventors of the present invention have studied the technology of reducing the unevenness of the solid content concentration in the in-plane direction, and as a result, they have found that by forming a first film based on a first material containing an electrolyte and an electrode active material on a support, and providing a second powder material containing an electrode active material and no liquid component on the first film, it is possible to manufacture a sheet-like electrode molded body with a single-layer structure having a high solid content concentration and little unevenness in the solid content concentration in the in-plane direction.
[0056] As described above, it is inferred that if a second material containing an electrode active material and no liquid component is given to the first film containing an electrolyte and an electrode active material, the liquid component (e.g., electrolyte) in the first film will infiltrate between the solid components in the second powder material (i.e., between the powders) due to capillary phenomena. Thus, the first film and the second powder material are mixed, and a single-layer electrode material film with a high solid component concentration but little uneven solid component concentration in the in-plane direction can be obtained. The obtained electrode material film can be used directly or pressed to become a sheet-like electrode molded body. Therefore, according to the manufacturing method of the electrode molded body involved in the present invention, a sheet-like electrode molded body with a high solid component concentration and little uneven solid component concentration in the in-plane direction can be manufactured.
[0057] In both Japanese Patent Application Publication No. 2017-183079 and Japanese Patent Application Publication No. 2018-147807, a two-layer electrode layer (equivalent to the electrode material film in the present invention) is formed, but there is no description of obtaining a single-layer electrode layer.
[0058] [1st step]
[0059] In the first step, a first material including an electrode active material and an electrolyte solution is provided on a support to form a first film based on the first material.
[0060] Hereinafter, “the first material including the electrode active material and the electrolyte solution” is also simply referred to as the first material.
[0061] Here, reference Figure 1The first step is described below. In the first step, the first material 22 is continuously applied to the support 10 moving in the direction of arrow X using the application mechanism 20 storing the first material 22, thereby forming a first film 24 made of the first material. Figure 1 It is a schematic cross-sectional view for explaining the first step and the second step in the method for producing the electrode molded body according to the present invention.
[0062] (Support)
[0063] In the first step, a support is used.
[0064] The support used in the first step is not particularly limited as long as it is a support that can form an electrode material film on the surface. In particular, from the viewpoint of continuously forming an electrode material film, it is preferred to use a long-sized support. In the case of a long-sized support, its width can be determined according to the size of the electrode material film, the width of the width direction of the molding component (e.g., a scraper, a roller) described later, etc.
[0065] In addition, the details of the support will be described later.
[0066] (First material)
[0067] The first material used in the first step includes an electrode active material and an electrolyte solution.
[0068] From the viewpoint of easiness of forming the first film, the solid content concentration in the first material is preferably 5 to 48 volume %, more preferably 15 to 40 volume %, and further preferably 20 to 35 volume %.
[0069] In other words, from the viewpoint of easiness of forming the first film, the concentration of the liquid component in the first material is preferably 52 to 95 volume %, more preferably 60 to 85 volume %, and even more preferably 65 to 80 volume %.
[0070] When the solid content concentration and the liquid content concentration are within the above ranges, it is easy to form a first film having a target thickness and solid content concentration.
[0071] The first material includes an electrode active material and an electrolyte solution, and may further include a conductive additive and other components as necessary.
[0072] The content of the electrode active material relative to the total volume of the first material is preferably 5% by volume to 48% by volume, more preferably 15% by volume to 40% by volume, and even more preferably 25% by volume to 35% by volume.
[0073] The content of the electrolyte solution relative to the total volume of the first material is preferably 95 to 52 volume %, more preferably 85 to 60 volume %, and even more preferably 75 to 65 volume %.
[0074] The content of the conductive auxiliary agent relative to the total volume of the first material is preferably 0.05% by volume to 5% by volume, more preferably 0.1% by volume to 3% by volume, and even more preferably 0.25% by volume to 2% by volume.
[0075] When the first material contains other components, the content of the other components relative to the total volume of the first material is preferably 0.01 to 1 volume %, more preferably 0.05 to 0.75 volume %, and even more preferably 0.1 to 0.5 volume %.
[0076] The electrode active material, the electrolyte, the conductive additive, and other components contained in the first material will be described in detail later.
[0077] (Provision of the first material)
[0078] In the first step, the first material is provided on a support.
[0079] The imparting mechanism for imparting the first material to the support may be any mechanism capable of imparting a desired amount of the first material to the support, and may be selected based on, for example, the viscosity of the first material, the thickness of the first film to be formed, etc.
[0080] As the imparting mechanism, in addition to a mechanism capable of imparting a desired amount of the first material to the support, a mechanism that imparts the first material in a film form to the support may be used. Specifically, the imparting mechanism includes a mechanism that intermittently or continuously supplies the first material to the support (for example, a mechanism using a hopper, screen printing, etc.), various coating mechanisms (for example, a coating mechanism using a slit coating method, a rod coating, a blade coating, etc.), and the like.
[0081] (Formation of the First Film)
[0082] In the first step, a first film is formed on a support. From the viewpoint of improving the uniformity of the thickness of the electrode material film, the first film preferably has high uniformity of thickness.
[0083] The formation of the first film can be a method of leveling the first material supplied intermittently or continuously to the support to form the first film with excellent thickness uniformity, or it can be a method of using a coating mechanism as a mechanism for imparting the first material to impart a film-like first material to the support with excellent thickness uniformity.
[0084] The mechanism for leveling the first material supplied onto the support is not particularly limited, and the same mechanism as the molding member (specifically, a scraper, a roller, etc.) described later can be used.
[0085] The thickness of the first film may be appropriately determined according to the thickness and solid content concentration of the electrode material film to be formed.
[0086] From the viewpoint of easily obtaining a single-layer electrode material film having a thickness and solid content concentration within the above ranges, the thickness of the first film is, for example, preferably 5 μm to 150 μm, more preferably 20 μm to 125 μm, and further preferably 25 μm to 100 μm.
[0087] like Figure 1 1 and 2 , when the first film is formed on the support, the support 10 is moved in the direction of arrow X relative to the fixed first material supply mechanism 20 , but the present invention is not limited to this embodiment.
[0088] When forming the first film, it is preferred to move the surface of the support body and the imparting mechanism of the first material relative to each other. In addition to the above method, it is also possible to move the imparting mechanism of the first material in one direction relative to the fixed support body, or to move both the support body and the molding component in one direction respectively.
[0089] However, in order to continuously form the electrode material film, that is, to form the electrode material film as a continuous film, it is preferable to use a long support and to move the long support by conveyance relative to a fixed scraper.
[0090] [Second step]
[0091] In the second step, a second powder material containing an electrode active material and no liquid component is provided on the first film.
[0092] Hereinafter, “the second powder material including the electrode active material and not including the liquid component” is also simply referred to as “the second powder material”.
[0093] Here, reference Figure 1 , the second step is described. In the second step, the second powder material 32 is applied to the first film 24 on the support 10 moving in the direction of the arrow X using the application mechanism 30 storing the second powder material 32. Thus, the second film 34 based on the second powder material 32 can be formed on the first film 24. In the second film 34, the electrolyte of the first film 24 is infiltrated due to the capillary phenomenon, and the first film 24 and the second film (second powder material) 34 are mixed to form a single-layer structure electrode material film (not shown).
[0094] (Second powder material)
[0095] The second powder material used in the second step contains an electrode active material but does not contain a liquid component.
[0096] In the present invention, "containing no liquid component" means "substantially containing no liquid component". "Substantially containing no liquid component" means that the content of the solid component relative to the total volume of the second powder material is 100% by volume, or that the presence of liquid components inevitably mixed in is allowed, but the presence of liquid components intentionally added is not allowed.
[0097] Furthermore, the "second powder material" means that the constituent material is powder.
[0098] That is, when the second powder material contains only the electrode active material as a powder and a solid component, it may contain the electrode active material as a powder and a solid component and components other than the electrode active material as a powder and a solid component (for example, a conductive additive).
[0099] The second powder material contains an electrode active material, and may contain a conductive auxiliary agent and other components in the form of a powder and a solid component (for example, an electrolyte such as ethylene carbonate) as necessary.
[0100] The content of the electrode active material relative to the total volume of the second powder material is preferably 90% by volume to 100% by volume, more preferably 95% by volume to 99.9% by volume, and even more preferably 97% by volume to 99.5% by volume.
[0101] The content of the conductive auxiliary agent relative to the total volume of the second powder material is preferably 10% by volume to 0% by volume, more preferably 5% by volume to 0.1% by volume, and even more preferably 3% by volume to 0.5% by volume.
[0102] When the component as a powder and a solid component among other components is included, the content of the component as a powder and a solid component among other components relative to the total volume of the second powder material is preferably 1 volume % to 0.01 volume %, more preferably 0.5 volume % to 0.05 volume %, and further preferably 0.25 volume % to 0.1 volume %.
[0103] In addition, the electrode active material, the conductive auxiliary agent, and other components contained in the second powder material are preferably selected from the same components as the electrode active material, the conductive auxiliary agent, and other components contained in the first film.
[0104] The details of the components in the form of powder and solid content among the electrode active material, the conductive additive, and other components contained in the second powder material will be described later.
[0105] (Provision of the second powder material)
[0106] In the second step, the second powder material is applied onto the first film formed on the support.
[0107] As a mechanism for imparting the second powder material to the first film, any mechanism can be used as long as it can impart the required amount of the second powder material to the first film. For example, it can be selected based on the bulk density of the second powder material, the thickness of the second film to be formed, etc.
[0108] Specific examples of the supplying mechanism include a mechanism for intermittently or continuously supplying the second powder material onto the support (for example, a hopper, a screw feeder, a disk feeder, a vibrating feeder, etc.), and a plurality of these mechanisms may be combined.
[0109] From the viewpoint of making the application of the second powder material onto the first film uniform, a limiting frame, a grid frame, or the like may be used in addition to the above-mentioned application mechanism.
[0110] (Preferred method)
[0111] It is speculated that in the second process, if the second powder material is applied to the first film, the liquid component (for example, electrolyte) in the first film infiltrates into the solid components (i.e., between the powders) in the second powder material due to the capillary phenomenon, and the first film and the second powder material are mixed, thereby forming a single-layer structure electrode material film.
[0112] In the second step, after the second powder material is applied to the first film, the second powder material applied to the first film is preferably leveled to limit the thickness of the laminate of the first film and the second powder material.
[0113] When the second powder material is applied on the first film, a laminate of the first film and the second powder material can be obtained. By leveling the second powder material applied on the first film, the thickness of the laminate of the first film and the second powder material is restricted.
[0114] In this way, the second powder material applied to the first film is leveled and the thickness of the laminate of the first film and the second powder material is limited, thereby applying pressure to both the first film and the second powder material, promoting the mixed existence of the first film and the second powder material, and promoting the discharge of the gas (specifically, air) contained in the second powder material. As a result, it is easy to form a single-layer electrode material film with a high solid content concentration and high uniformity of solid content concentration in the in-plane direction.
[0115] Hereinafter, a preferred embodiment of the second step will be described.
[0116] -Using molded parts-
[0117] In the second step, after the second powder material containing the electrode active material and no liquid component is applied to the first film, the second powder material applied to the first film is preferably flattened by a molding member.
[0118] Furthermore, the second step is also preferably the following step: after imparting a second powder material containing an electrode active substance and not containing a liquid component to the first film, a film is placed on the second powder material imparted to the first film, and the second powder material is pressed from the film through a molding component, thereby flattening the second powder material imparted to the first film and limiting the thickness of the stack of the first film and the second powder material.
[0119] Here, as a molding part, as long as it is a part that can flatten the surface of the second powder material, there is no particular restriction, for example, plate-shaped parts such as scrapers and scrapers, rollers, flat plate punches, roller presses, etc. can be cited. Among them, from the viewpoint of easily controlling the thickness of the electrode material film and easily making it uniform, as a molding part, a scraper or a roller is preferred. In addition, on the molding part, as a part that transmits vibration, an ultrasonic vibration horn, a piezoelectric vibration horn, etc. can be connected. By connecting a part that transmits vibration on the molding part, the molding part can be vibrated. In particular, it is preferred to use a molding part that performs ultrasonic vibration.
[0120] refer to Figure 2 and Figure 3 , the second powder material applied to the first film is flattened by a molding member, and the thickness of the laminate of the first film and the second powder material is limited. Figure 2 and Figure 3 This is a schematic cross-sectional view for explaining the manner in which the second powder material applied to the first film is leveled by the molding component in the second step. Figure 2 An example of using a scraper as a forming component is shown in FIG. Figure 3 , an example is shown in which a roller is used as a molding member and a film is inserted between the roller and the second powder material.
[0121] exist Figure 2 In the example shown, the scraper 40 as the molding member is used to flatten the second film 34 based on the second powder material 32 applied to the first film 24 formed on the support 10, and to limit the thickness of the stack of the first film 24 and the second film 34 based on the second powder material 32. At this time, it can also be said that the stack of the first film 24 and the second film 34 is pressurized by the scraper 40.
[0122] like Figure 2As shown, the scraper 40 is arranged in such a manner that its front end contacts the second film 34 and maintains a constant distance from the surface of the support 10. By moving it on the support 10 along the arrow X direction, the stack of the first film 24 and the second film 34 formed on the support 10 passes through the gap between the surface of the support 10 and the front end of the scraper 40, and pressure is applied to the stack to flatten the second film 34. And, at this time, the thickness of the stack can be limited to the same thickness as the above-mentioned gap. In this way, if pressure is applied to the stack by the scraper 40, the mixed existence of the first film 24 and the second film (i.e., the second powder material) 34 is promoted, so that a single-layer structure electrode material film 50 can be obtained.
[0123] exist Figure 3 In the example shown, the roller 60 as the molding member is used to flatten the second film 34 based on the second powder material 32 applied to the first film 24 formed on the support 10 via the film 62, and the thickness of the laminate of the first film 24 and the second film 34 based on the second powder material 32 is limited. At this time, it can also be said that the laminate of the first film 24 and the second film 34 is pressurized by the roller 60.
[0124] like Figure 3 As shown, the roller 60 is arranged so that its outer peripheral surface contacts the second film 34 and is kept at a constant distance from the surface of the support 10. By moving the roller 60 on the support 10 in the direction of arrow X, the laminate of the first film 24 and the second film 34 formed on the support 10 passes through the gap between the surface of the support 10 and the front end of the roller 60, and pressure is applied to the laminate to flatten the second film 34. Figure 3 In the example shown, a thin film 62 is inserted between the second film 34 and the roller 60. By inserting the thin film 62, it is possible to suppress the volatilization of the electrolyte from the stack. The roller 60 rotates while contacting the stack of the first film 24 and the second film 34 via the thin film 62, thereby compacting the stack and limiting the thickness. In this way, if pressure is applied to the stack by the roller 60, the mixed existence of the first film 24 and the second film (i.e., the second powder material) 34 is promoted, so that a single-layer structure electrode material film 50 can be obtained.
[0125] In addition, when the electrolyte solution is allowed to volatilize from the laminate, the film 62 can be omitted.
[0126] As described above, the laminate of the first film and the second film is pressurized by a forming member such as a scraper or a roller. At this time, the laminate of the first film and the second film is pressurized by the forming member until the thickness of the electrode material film of the single-layer structure obtained after the pressurization becomes the above-mentioned thickness, specifically, becomes the set thickness in the range of 50 μm to 250 μm.
[0127] In addition, as the molding member, a vibrating blade or a roller is preferably used.
[0128] In other words, in the second step, the second powder material applied onto the first film is preferably leveled by a vibrating scraper or roller.
[0129] The vibration of the forming parts such as the scraper and the roller further promotes the mixing of the first film and the second powder material, and also promotes the discharge of the gas (specifically, air) contained in the second powder material. As a result, a single-layer electrode material film with a high solid content concentration and a more excellent uniformity of the solid content concentration in the in-plane direction can be formed.
[0130] In addition, the vibration direction when vibrating the molded component is not particularly limited. Furthermore, the vibration of the molded component may be continuous or intermittent.
[0131] The amplitude of the vibration of the molded component is, for example, preferably 0.1 μm to 60 μm, and more preferably 1 μm to 10 μm.
[0132] Furthermore, the vibration frequency of the molding component is preferably, for example, 50 Hz to 40,000 Hz, and more preferably 100 Hz to 37,500 Hz. In addition, the vibration frequency of the molding component may include a plurality of frequencies. For example, the vibration of the molding component may be a vibration in which a plurality of frequency peaks such as 150 Hz, 300 Hz, and 450 Hz are detected.
[0133] Here, the amplitude and frequency of the vibration can be measured by an acceleration sensor or a vibration measuring instrument. In addition, when measuring the vibration of the molded component, when multiple frequency peaks are detected, the frequency of the minimum value is set as the "frequency of the vibration of the molded component", and the amplitude at this frequency is set as the "amplitude of the vibration of the molded component". For example, with respect to the vibration of the molded component, when multiple frequency peaks such as 150 Hz, 300 Hz, and 450 Hz are detected, 150 Hz is set as the "frequency of the vibration of the molded component", and the amplitude at the frequency of 150 Hz is set as the "amplitude of the vibration of the molded component".
[0134] Regarding the second step, Figure 2 FIG. 4 shows a mode in which the support body 10 moves relative to the fixed scraper 40 along the direction of arrow X. Figure 3 4 shows a mode in which the support body 10 moves in the arrow X direction relative to the fixed roller 60, but the present invention is not limited to this mode.
[0135] When leveling the second powder material imparted to the first film formed on the support, it is preferred to move the support surface and the molding component relative to each other. In addition to the above method, the molding component may be moved in one direction relative to the fixed support, or both the support and the molding component may be moved in one direction respectively.
[0136] However, in order to continuously form the electrode material film, that is, to form the electrode material film as a continuous film, it is preferable to use a long support and to convey the long support relative to the fixed molding member.
[0137] Here, as a mechanism for moving the support body, a known conveying mechanism can be used. Specifically, as the conveying mechanism for the support body, for example, a belt conveyor, a linear slide guide, a cross roller conveyor, etc. can be used.
[0138] In addition, in the second step, the second powder material may be applied to the first film on the support, and after the second film is formed, the laminate of the support, the first film, and the second film may be divided in the surface direction of the support. In addition, the division of the laminate is preferably performed before the second powder material applied to the first film is flattened by the molding component, that is, before the second film is flattened by the molding component.
[0139] That is, the method for producing the electrode molded body according to the present invention is preferably:
[0140] The second step is a step of providing a second powder material containing an electrode active material and no liquid component on the first film to form a second film based on the second powder material.
[0141] Furthermore, the method further includes a third step of dividing the laminated body obtained in the second step, in which the support, the first film, and the second film are laminated in this order, in the surface direction of the support.
[0142] In this method, a laminated body having a large area is formed and then divided into laminated bodies having a smaller area (for example, the area of the electrodes).
[0143] Furthermore, it is preferable that the method further comprises a step of flattening the second film by a molding member after the step of dividing the laminated body in which the support, the first film, and the second film are sequentially laminated in the surface direction of the support.
[0144] That is, the method for producing the electrode molded body according to the present invention is preferably:
[0145] The second step is a step of providing a second powder material containing an electrode active material and no liquid component on the first film to form a second film based on the second powder material.
[0146] And, further comprising:
[0147] A third step of dividing the laminate obtained in the second step, in which the support, the first film, and the second film are sequentially laminated, in a surface direction of the support; and
[0148] In the fourth step, the second film of the stacked body divided by the film forming material is flattened.
[0149] In the above aspect, it is preferable to use a support body in which at least the surface in contact with the first film in advance can be divided in the surface direction.
[0150] As the above-mentioned support, for example, a plurality of metal layers (layers that become collectors) of desired sizes can be separated from each other and arranged on a resin film, and the resin film portion between the metal layers is bent to the side opposite to the metal layer side so that the separated metal layers are in contact without gaps. In such a support, by dividing the metal layers in contact without gaps, the laminated body in which the support, the first film and the second film are sequentially stacked can be divided in the surface direction of the support.
[0151] [Step 3]
[0152] The method for manufacturing an electrode molded body involved in the present invention preferably further includes a third step, in which, after the second powder material imparted to the first film is leveled in the second step and the thickness of the stack of the first film and the second powder material is limited, the stack with limited thickness (specifically, the electrode material film with a single-layer structure) is compressed by a vibrating pressurizing component.
[0153] By including the third step, the first layer and the second powder material in the laminate can be further mixed. In addition, by including the third step, the density of the laminate can be increased, and the density and thickness of the solid component can be uniformed in the plane. As a result, a single-layer electrode material film having a high solid component concentration and a higher uniformity of the solid component concentration in the thickness direction can be obtained.
[0154] (Compression of laminated body)
[0155] In this process, for example, Figure 4 In the method shown, a laminate (specifically, a single-layer electrode material film) having a limited thickness is compressed by a vibrating pressurizing member. Figure 4 This is a schematic cross-sectional view for explaining a step of compressing a single-layer electrode material film (a laminated body after thickness control) by a vibrating pressurizing member.
[0156] exist Figure 4 The following process is shown in FIG. 1 : by using a scraper 40 to flatten the second film 34, flattening the first film and the second powder material on the support 10, and limiting the thickness of the stack of the first film and the second powder material, a single-layer electrode material film (equivalent to a stack with a limited thickness) 50 is formed, and then the formed single-layer electrode material film 50 is compressed by a vibrating pressurizing component. Figure 4In the example shown, a film 72 is placed on a single-layer electrode material film 50 formed on a support 10, and a vibrating pressure roller (an example of a pressure member) 70 is pressed from above the film 72, thereby pressurizing the single-layer electrode material film 50. By pressurizing the electrode material film 50, a compressed electrode material film 52 can be obtained.
[0157] In addition, this process is not limited to Figure 4 The method shown in the figure may be, for example, a method of using a vibrating pressure plate, a pressure roller pair, and a punch as a pressure member. In addition, in this process, as a method of vibrating the pressure member, a method of connecting a vibrator, a vibration horn, etc. to the above-mentioned pressure member may be cited.
[0158] The pressure at the time of compressing the electrode material film is preferably 0.01 MPa to 100 MPa, more preferably 0.1 MPa to 50 MPa, and particularly preferably 0.2 MPa to 10 MPa.
[0159] Furthermore, the amplitude of vibration of the vibrating pressurizing member and the frequency of vibration of the pressurizing member are preferably the same conditions as the amplitude of vibration of the molding member and the frequency of vibration of the molding member described above, respectively.
[0160] In addition, in this step, from the viewpoint of further reducing the non-uniformity of the solid content concentration in the in-plane direction, it is preferable to use a pressurizing member that performs ultrasonic vibration.
[0161] In addition, in this process, a vibrating pressurizing member is used, but the pressurizing member may also be in a non-vibrating state. That is, after the second powder material applied to the first film is leveled and the thickness of the stack of the first film and the second powder material is limited, the stack (specifically, the electrode material film of the single-layer structure) with limited thickness may be compressed by the non-vibrating pressurizing member.
[0162] Furthermore, in this step, the electrode material film may be pressurized (compressed) in stages by appropriately changing the pressurizing member, pressurizing conditions, and the like.
[0163] In this step, it is preferred that the pressurizing member and the stacked product (specifically, the support on which the electrode material film is formed) are relatively moved.
[0164] In the present invention, "moving the pressurizing member and the stacked object relative to each other" includes moving the pressurizing member in one direction relative to the stacked object, moving the stacked object in one direction relative to the pressurizing member, and moving the pressurizing member and the stacked object in one direction respectively, but preferably moving the stacked object in one direction relative to the pressurizing member.
[0165] The mechanism for moving the stacked product (specifically, the support on which the electrode material film is formed) is not limited, and a known conveying mechanism can be used, for example, a belt conveyor, a linear slide guide, and a cross roller conveyor.
[0166] In this step, from the viewpoint of improving moldability, the laminate heated at, for example, 30° C. to 100° C. may be pressurized (compressed).
[0167] As described above, by going through the first step and the second step (preferably, further going through the third step), it is possible to form an electrode material film having a single-layer structure as a mixture of the first film and the second powder material.
[0168] The electrode material film of the single-layer structure can be maintained as it is or can be further pressed to form a sheet-shaped electrode molded body.
[0169] 〔Other processes〕
[0170] The method for producing the electrode molded body according to the present invention may include other steps.
[0171] As another step, for example, when the support is a release paper, there is mentioned a step of transferring the electrode material film formed on the release paper to the current collector.
[0172] Hereinafter, the support body and the molding member used in the method for producing the molded body for an electrode according to the present invention will be described in detail.
[0173] Furthermore, the details of the components constituting the first material and the second powder material will also be described.
[0174] [Support]
[0175] As the support, specifically, a current collector is mentioned as a preferred support.
[0176] The current collector which is an example of the support is not particularly limited, and a known current collector (positive electrode current collector and negative electrode current collector) can be used.
[0177] Examples of the positive electrode current collector include aluminum, aluminum alloys, stainless steel, nickel, and titanium. The positive electrode current collector is preferably aluminum or an aluminum alloy. The positive electrode current collector may be aluminum having a coating layer containing one or more of carbon, nickel, titanium, silver, gold, platinum, and vanadium oxide on the surface.
[0178] Examples of the negative electrode current collector include aluminum, copper, copper alloys, stainless steel, nickel, and titanium. The negative electrode current collector is preferably aluminum, copper, copper alloys, or stainless steel, more preferably copper or a copper alloy. The negative electrode current collector may be copper or stainless steel having a coating layer containing one or more of carbon, nickel, titanium, silver, and lithium on the surface.
[0179] As the current collector, aluminum foil (including aluminum foil having the above-mentioned coating layer on the surface) and copper foil (including copper foil having the above-mentioned coating layer on the surface) are preferred. Usually, aluminum foil is used as the current collector in the positive electrode. Usually, copper foil is used as the current collector in the negative electrode.
[0180] Furthermore, the support may be a laminate of a metal layer and a resin film exemplified as the above-mentioned positive electrode collector or negative electrode collector. As the resin film used for the laminate, there can be cited resin films such as polyethylene terephthalate (PET) film, polypropylene (PP) film, polyethylene (PE) film, cyclic olefin polymer (COP, COC) film, triacetyl cellulose (TAC) polyimide (PI) film, and polyamide (PA) film.
[0181] Furthermore, as an example of the support, a release material can be mentioned.
[0182] Examples of the release material as an example of the support include release paper (for example, release paper manufactured by LINTEC Corporation), a film having a release layer, and paper having a release layer. Among them, release paper is preferred.
[0183] Furthermore, when a release material is used as the support, the electrode material film formed on the release material can be transferred to the current collector by utilizing the releasability of the release material.
[0184] From the viewpoint of transportability and the like, the thickness of the support (preferably a current collector) is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more.
[0185] From the viewpoint of flexibility and lightness, the thickness is preferably 100 μm or less, more preferably 70 μm or less, and particularly preferably 50 μm or less.
[0186] The thickness of the support is measured by the same method as the thickness of the electrode material film having a single-layer structure.
[0187] The size of the support is not limited and may be determined according to the size of the electrode molded body to be produced, the sizes of various members used in the production process, and the like.
[0188] Furthermore, in this step, as the support body conveying mechanism, the support body conveying mechanism in the first step and the second step can be adopted.
[0189] [Molding parts]
[0190] Preferred examples of the molding member include a blade and a roller.
[0191] (Scraper)
[0192] The scraper is a component with a plate-like shape. The shape, size, material, etc. of the contact portion with the second powder material (or the second film) can be appropriately determined according to the various physical properties of the second powder material (or the second film) (type of electrode active substance, solid content concentration, composition of the electrolyte (viscosity, surface tension), etc.), the size and thickness of the electrode material film formed, etc.
[0193] Furthermore, it is preferred that the electrode material is less likely to adhere to the portion of the scraper in contact with the second powder material (or the second film). For example, it is preferred that at least the surface of the scraper exhibits releasability.
[0194] For example, the scraper may be made of fluorine-based resin such as polytetrafluoroethylene (PTFE), resin such as polyetheretherketone (PEEK), metal such as stainless steel, aluminum, iron, superhard alloy, or ceramic.
[0195] Furthermore, in order to impart mold release properties to the surface, the blade may include a surface layer exhibiting mold release properties (for example, a surface layer containing a fluorine-based resin, a surface layer containing silicon-based particles and a resin).
[0196] Furthermore, from the viewpoint of improving the friction resistance, the blade may have a high hardness coating of titanium oxide, titanium nitride (TiN), tungsten carbide or the like on the metal or ceramic blade body.
[0197] (Roller)
[0198] The roller is a component whose outer peripheral surface can rotate. The size, material, etc. can be appropriately determined based on the various physical properties of the second powder material (or the second film) (type of electrode active substance, solid content concentration, composition of the electrolyte (viscosity, surface tension), etc.), the size and thickness of the electrode material film formed, etc.
[0199] The material constituting the outer peripheral surface of the roller may be the same as that of the blade, and may have a surface layer exhibiting mold release properties.
[0200] The outer diameter of the roller is not particularly limited, but may be, for example, 20 mm to 30 mm.
[0201] Furthermore, since the roller rotates, the friction coefficient between the outer peripheral surface and the second powder material (or the second film) can be regarded as 0. However, as a result, the adhesion to the second powder material (or the second film) may sometimes become high. Figure 3 As shown, it is preferable to insert a thin film between the second powder material (or the second film) and the outer peripheral surface of the roller.
[0202] [Components constituting the first material and components constituting the second powder material]
[0203] The first material contains at least an electrode active material and an electrolyte. From the viewpoint of facilitating the formation of the first film, as described above, the solid content concentration in the first material is preferably 10% to 45% by volume relative to the total volume of the first material.
[0204] Furthermore, the second powder material contains at least an electrode active material.
[0205] (Electrode Active Material)
[0206] The electrode active material is a material that can insert and release ions of a metal element belonging to Group 1 or Group 2 of the periodic table. The electrode active material is contained in a solid component.
[0207] Examples of the electrode active material include a positive electrode active material and a negative electrode active material.
[0208] -Positive electrode active material-
[0209] The positive electrode active material is not limited, and a known electrode active material used in a positive electrode can be used. The positive electrode active material is preferably a positive electrode active material that can reversibly insert and release lithium ions.
[0210] Specific examples of the positive electrode active material include transition metal oxides and elements that can form a complex with lithium (for example, sulfur). Among the above, the positive electrode active material is preferably a transition metal oxide.
[0211] The transition metal oxide is preferably a transition metal oxide containing at least one transition metal element (hereinafter referred to as “element Ma”) selected from the group consisting of Co (cobalt), Ni (nickel), Fe (iron), Mn (manganese), Cu (copper) and V (vanadium).
[0212] When the transition metal oxide contains Li and the element Ma, the molar ratio of Li to Ma (Li / Ma) is preferably 0.3 to 2.2.
[0213] Furthermore, the transition metal oxide may contain at least one transition metal element (hereinafter referred to as "element Mb") selected from the group consisting of Group 1 elements other than lithium, Group 2 elements, Al (aluminum), Ga (gallium), In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony), Bi (bismuth), Si (silicon), P (phosphorus) and B (boron). The content of element Mb is preferably 0 mol% to 30 mol% relative to the amount of substance of element Ma.
[0214] Examples of the transition metal oxide include transition metal oxides having a layered rock salt structure, transition metal oxides having a spinel structure, lithium-containing transition metal phosphate compounds, lithium-containing transition metal halophosphate compounds, and lithium-containing transition metal silicate compounds.
[0215] Examples of transition metal oxides having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]) and LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide).
[0216] Examples of transition metal oxides having a spinel structure include LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.
[0217] As lithium-containing transition metal phosphate compounds, for example, there can be mentioned olivine-type iron phosphates (for example, LiFePO4 and Li3Fe2(PO4)3), pyrophosphate iron salts (for example, LiFeP2O7), cobalt phosphates (for example, LiCoPO4) and monoclinic NASICON-type vanadium phosphates (for example, Li3V2(PO4)3 (lithium vanadium phosphate)).
[0218] Examples of lithium-containing transition metal halophosphate compounds include iron fluorophosphates (eg, Li2FePO4F), manganese fluorophosphates (eg, Li2MnPO4F), and cobalt fluorophosphates (eg, Li2CoPO4F).
[0219] Examples of lithium-containing transition metal silicate compounds include Li 2 FeSiO 4 , Li 2 MnSiO 4 , and Li 2 CoSiO 4 .
[0220] The transition metal oxide is preferably a transition metal oxide having a layered rock salt structure, and more preferably selected from LiCoO2 (lithium cobalt oxide [LCO]), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]) and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one compound selected from the group consisting of O2 (lithium nickel manganese cobalt oxide [NMC]).
[0221] The positive electrode active material may be a commercial product or a synthetic product produced by a known method (eg, calcination method). For example, the positive electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.
[0222] Furthermore, the positive electrode active material may have a carbon coating on its surface.
[0223] The shape of the positive electrode active material is not limited, but is preferably in the form of particles from the viewpoint of handleability.
[0224] The volume average particle size of the positive electrode active material is not limited, and can be, for example, 0.1 μm to 50 μm. The volume average particle size of the positive electrode active material is preferably 0.3 μm to 40 μm, and more preferably 0.5 μm to 30 μm.
[0225] The volume average particle size of the positive electrode active material is 0.3 μm or more, thereby preventing the positive electrode active material from splashing during operation. The volume average particle size of the positive electrode active material is 40 μm or less, thereby making it easy to adjust the thickness of the electrode molded body and preventing the generation of voids during the molding process.
[0226] The volume average particle size of the positive electrode active material is measured by the following method.
[0227] A dispersion containing less than 0.1% by mass of a positive electrode active material is prepared by mixing a positive electrode active material with a solvent (e.g., pure water, ethanol, heptane, octane, toluene or xylene). The dispersion irradiated with 1kHz ultrasonic waves for 10 minutes is set as a measurement sample. Using a laser diffraction / scattering particle size distribution measuring device (e.g., LA-960 manufactured by HORIBA, Ltd.) and at a temperature of 25°C, 50 data readings are performed, and the volume average particle size is calculated based on the volume frequency particle size distribution. A quartz colorimetric cell is used in the measuring cell. The above measurement is performed using 5 samples, and the average of the measured values is set as the volume average particle size of the positive electrode active material. For other detailed conditions, refer to "JISZ 8828:2013" as needed.
[0228] As a method for adjusting the particle size of the positive electrode active material, for example, a method using a pulverizer, a disintegrator, or a classifier can be cited. In addition, as a method for adjusting the particle size of the positive electrode active material, a known grinding method can be applied.
[0229] The first material and the second powder material may each contain a single type of positive electrode active material, or may contain two or more types of positive electrode active materials.
[0230] Furthermore, even when the first material and the second powder material each contain one type of positive electrode active material, positive electrode active materials having different particle sizes may be used in combination.
[0231] -Negative electrode active material-
[0232] The negative electrode active material is not limited, and a known electrode active material used in a negative electrode can be used. The negative electrode active material is preferably a negative electrode active material that can reversibly insert and release lithium ions.
[0233] As the negative electrode active material, for example, carbonaceous materials, metal oxides (for example, tin oxide), silicon oxide, metal composite oxides, lithium monomers, lithium alloys (for example, lithium aluminum alloys) and metals that can form alloys with lithium (for example, Sn, Si and In) can be cited. Among the above, from the viewpoint of reliability, the negative electrode active material is preferably a carbonaceous material or a lithium composite oxide.
[0234] Carbonaceous materials are materials consisting substantially of carbon.
[0235] Examples of carbonaceous materials include petroleum pitch, carbon black (e.g., acetylene black), graphite (e.g., natural graphite and artificial graphite (e.g., vapor-grown graphite)), hard carbon, and carbonaceous materials obtained by calcining synthetic resins (e.g., polyacrylonitrile (PAN) and furfuryl alcohol resin). Examples of carbonaceous materials include carbon fibers (e.g., polyacrylonitrile carbon fibers, cellulose carbon fibers, pitch carbon fibers, vapor-grown carbon fibers, dehydrated PVA (polyvinyl alcohol) carbon fibers, lignin carbon fibers, glassy carbon fibers, and activated carbon fibers). Examples of graphite include mesophase microspheres, graphite whiskers, and flat graphite.
[0236] In the present invention, "flat plate shape" means a shape having two main planes facing in opposite directions.
[0237] As the metal composite oxide, a metal composite oxide capable of occluding and releasing lithium is preferred.
[0238] From the viewpoint of high current density charge and discharge characteristics, the metal composite oxide capable of occluding and releasing lithium preferably contains at least one element selected from the group consisting of titanium and lithium.
[0239] The metal oxide and the metal composite oxide are particularly preferably amorphous oxides.
[0240] The metal oxide and the metal composite oxide are also preferably chalcogenides. Chalcogenides are reaction products between metal elements and elements of Group 16 in the periodic table.
[0241] Among the compound group consisting of amorphous oxides and chalcogenides, amorphous oxides and chalcogenides of semimetallic elements are also preferred, and oxides and chalcogenides of at least one element selected from the group consisting of elements of Groups 13 to 15 in the periodic table, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi are more preferred.
[0242] The negative electrode active material preferably further contains titanium. The volume change during the storage and release of lithium ions is small, so the rapid charge and discharge characteristics are excellent, and from the perspective of suppressing the degradation of the electrode and increasing the life of the lithium ion secondary battery, the negative electrode active material containing titanium is preferably Li4Ti5O 12 (lithium titanate [LTO]).
[0243] The negative electrode active material may be a commercial product or a synthetic product produced by a known method (eg, calcination method). For example, the negative electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.
[0244] The negative electrode active material is available as, for example, CGB20 (Nippon Graphite Industry Co., Ltd.).
[0245] The composition of the negative electrode active material was measured using inductively coupled plasma (ICP) emission spectrometry.
[0246] The shape of the negative electrode active material is not limited, but is preferably in the form of particles from the viewpoint of easy handling and easy control of uniformity during mass production.
[0247] The volume average particle size of the negative electrode active material is preferably 0.1 μm to 60 μm, more preferably 0.3 μm to 50 μm, and particularly preferably 0.5 μm to 40 μm.
[0248] The volume average particle size of the negative electrode active material is measured by a method based on the method for measuring the volume average particle size of the positive electrode active material described above.
[0249] Examples of methods for adjusting the particle size of the negative electrode active material include a method using a pulverizer or a classifier.
[0250] The first material and the second powder material may each contain a single type of negative electrode active material, or may contain two or more types of negative electrode active materials.
[0251] The surfaces of the positive electrode active material and the negative electrode active material may be coated with a surface coating agent, respectively. As the surface coating agent, for example, a metal oxide containing Ti, Nb, Ta, W, Zr, Si or Li may be cited. As the above-mentioned metal oxide, for example, titanate spinel, tantalum oxide, niobium oxide and lithium niobate compounds may be cited.
[0252] (Electrolyte)
[0253] There is no particular limitation on the electrolyte, and a known electrolyte can be used. For example, an electrolyte containing an electrolyte and a solvent can be cited. As a specific electrolyte, for example, an electrolyte containing a lithium salt compound as an electrolyte and a carbonate compound as a solvent can be cited.
[0254] As the lithium salt compound, for example, lithium hexafluorophosphate can be mentioned. The electrolyte solution may contain a single lithium salt compound, or may contain two or more lithium salt compounds.
[0255] As carbonate compounds, for example, chain carbonate compounds such as ethyl methyl carbonate (also referred to as EMC), dimethyl carbonate (also referred to as DMC), diethyl carbonate (DEC) and cyclic carbonate compounds such as ethylene carbonate (also referred to as EC) and propylene carbonate (also referred to as PC) can be cited. The electrolyte can include a single carbonate compound, can include two or more carbonate compounds, and can also use more than one chain carbonate compound and more than one cyclic carbonate compound simultaneously.
[0256] As the electrolyte contained in the electrolytic solution, for example, a well-known inorganic solid electrolyte can be used.
[0257] As a component of the electrolytic solution, for example, an ionic liquid can be used. The ionic liquid can be used as an electrolyte or as a solvent.
[0258] (Solvent)
[0259] The first material may contain, as a liquid component, a solvent other than the solvent contained as a component of the electrolytic solution (hereinafter, also simply referred to as a “solvent”).
[0260] Examples of the solvent include alcohol compound solvents, ether compound solvents, amide compound solvents, amino compound solvents, ketone compound solvents, aromatic compound solvents, aliphatic compound solvents, and nitrile compound solvents.
[0261] The boiling point of the solvent is preferably 50° C. or higher, more preferably 70° C. or higher, at normal pressure (ie, 1 atmosphere). The upper limit of the boiling point of the solvent is preferably 250° C. or lower, more preferably 220° C. or lower, at normal pressure (ie, 1 atmosphere).
[0262] The first material may contain a single solvent or two or more solvents.
[0263] In addition, the liquid component in the first material, that is, the component in the first material that is liquid at 25° C., is preferably liquid even at -10° C., and is preferably liquid even at -20° C. That is, the component in the first material that is liquid at 25° C. is preferably a component that does not solidify at -10° C., and is preferably a component that does not solidify at -20° C.
[0264] (Conductive additive)
[0265] From the viewpoint of improving the electron conductivity of the electrode active material, it is preferred that the first material and the second powder material each contain a conductive auxiliary agent. The conductive auxiliary agent is not limited, and a known conductive auxiliary agent can be used.
[0266] The conductive auxiliary agent is contained in the solid component.
[0267] As conductive aids, for example, graphite (for example, natural graphite and artificial graphite), carbon black (for example, acetylene black, Ketjen black and furnace black), amorphous carbon (for example, needle coke), carbon fiber (for example, vapor-grown carbon fiber and carbon nanotube), other carbonaceous materials (for example, graphene and fullerene), metal powder (for example, copper powder and nickel powder), metal fiber (for example, copper fiber and nickel fiber) and conductive polymer (for example, polyaniline, polypyrrole, polythiophene, polyacetylene and polyphenylene derivatives) can be cited.
[0268] The first material and the second powder material may each contain a single conductive auxiliary agent, or may contain two or more conductive auxiliary agents.
[0269] (Other ingredients)
[0270] The first material and the second powder material may contain a binder, a dispersant, other additives, etc. in addition to the above components. However, in either the first material or the second powder material, from the viewpoint of improving energy density, the binder content is preferably low, and more preferably no binder is contained.
[0271] Examples of the binder include fluorine-containing resins, hydrocarbon thermoplastic resins, acrylic resins, and urethane resins.
[0272] Furthermore, the dispersant may be any known dispersant as long as it can disperse the dispersion object.
[0273] Furthermore, as other additives, known additives added to electrodes can be used.
[0274] (Method for preparing the first material and the second powder material)
[0275] The first material can be prepared by, for example, mixing an electrode active material, an electrolyte solution, and other components (for example, a conductive additive) used as necessary.
[0276] Furthermore, the second powder material can be prepared by, for example, mixing an electrode active material and other components (for example, a conductive auxiliary agent) used as necessary.
[0277] Examples of the mixing method include methods using a ball mill, a bead mill, a planetary mixer, a blade mixer, a roll mill, a kneader, or a disk mill.
[0278] <<Molded article for sheet electrode>>
[0279] The sheet-shaped electrode molded body obtained by the method for producing a sheet-shaped electrode molded body according to the present invention can be used as various electrodes. In addition, the sheet-shaped electrode molded body can be used as an electrode as it is, or the sheet-shaped electrode molded body can be further processed to be used as an electrode.
[0280] The sheet-shaped molded body for an electrode is preferably a molded body for an electrode of a semi-solid secondary battery.
[0281] From the viewpoint of improving battery performance (eg, discharge capacity and output characteristics), the sheet-shaped electrode molded body preferably has a thickness of 50 μm to 250 μm and a solid content of 50 to 80 volume % similarly to the above-mentioned single-layer electrode material film.
[0282] The thickness of the sheet-shaped electrode molded body is measured by the same method as the thickness of the single-layer electrode material film. The solid content concentration of the sheet-shaped electrode molded body is also calculated by the same method as the solid content concentration of the single-layer electrode material film.
[0283] The sheet-shaped electrode molded body obtained by the method for manufacturing an electrode molded body of the present invention is formed on a support, but in the sheet-shaped electrode molded body with a support, the smoothness of the support tends to be high. This is because, in the method for manufacturing an electrode molded body of the present invention, a sheet-shaped electrode molded body having a high solid content concentration can be manufactured, but a large pressure is not required during the process.
[0284] Specifically, when the support is a current collector, the arithmetic mean roughness Ra of the current collector in the sheet-shaped electrode molded body with a current collector is preferably 0.1 nm to 1000 nm, and more preferably 1 nm to 30 nm.
[0285] Furthermore, in the case where the support is a current collector, in the sheet-shaped electrode molded body with the current collector, a coating layer tends to be unnecessary on the surface. Usually, the coating layer of the current collector is provided to make the surface rough. By making the surface of the current collector rough, the adhesion with the material imparted to the current collector can be improved. In the method for manufacturing the electrode molded body involved in the present invention, a first film based on a first material containing an electrolyte is formed on the current collector as a support, so that the adhesion effect on the current collector is manifested by the action of the electrolyte, and therefore a coating layer in the current collector is not necessary.
[0286] Therefore, when the support is a current collector, the current collector in the sheet-shaped electrode molded body with a current collector preferably has no coating layer.
[0287] Moreover, in the sheet-shaped electrode molded body, the content of the conductive aid having a needle-like shape or a fibrous shape tends to be high. In order to manufacture a sheet-shaped electrode molded body having a high solid content concentration and a uniform solid content concentration, it is usually used after applying a very high pressure to an electrode material containing a large amount of solid components such as a conductive aid and an electrode active material and a small amount of electrolyte to be uniformly dispersed. Due to the high pressure during the dispersion treatment, the needle-like shape or the fibrous shape of the conductive aid is destroyed (for example, cut), so there is less conductive aid having a needle-like shape or a fibrous shape remaining in the obtained sheet-shaped electrode molded body. In the manufacturing method of the electrode molded body involved in the present invention, a first material containing more electrolyte than the above-mentioned electrode material can be used, so the pressure for uniformly dispersing the components constituting the first material can be reduced. As a result, in the sheet-shaped electrode molded body manufactured by the manufacturing method of the electrode molded body involved in the present invention, the content of the conductive aid having a needle-like shape or a fibrous shape becomes high.
[0288] Example
[0289] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited thereto.
[0290] In addition, each process in each example mentioned later was performed in the drying room (low dew point room) of 22 degreeC.
[0291] [Preparation of the first material (1-1) for positive electrode]
[0292] (1) After LiPF6 (electrolyte) was mixed into a mixed solution of ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC), vinylene carbonate (VC) was further mixed in. 64 g of the obtained mixed solution was taken out and used as electrolyte X1.
[0293] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 1 g of a conductive aid (Ketjen Black) and 80 g of a positive electrode active material (lithium iron phosphate) were stirred at 1500 rpm (revolutions per minute, the same applies hereinafter) for 30 seconds to prepare a kneaded product Y1 (81 g).
[0294] (3) Electrolyte X1 (64 g) was added to kneaded product Y1 (81 g), and the mixture was stirred at 1500 rpm for 120 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a first positive electrode material (1-1).
[0295] The volume ratio of the solid content to the liquid content of the obtained first positive electrode material (1-1) was 31:69. That is, the solid content concentration of the first positive electrode material (1-1) was 31% by volume.
[0296] [Preparation of the first material (1-2) for positive electrode]
[0297] An electrolyte solution X1 (64 g) was obtained in the same manner as in the preparation of the first material (1-1) for the positive electrode.
[0298] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 0.4 g of a conductive agent (Ketjen Black) and 34.1 g of a positive electrode active material (lithium iron phosphate) were stirred at 1500 rpm for 30 seconds to prepare a kneaded product Y2 (34.5 g).
[0299] (3) Electrolyte X1 (64 g) was added to kneaded product Y2 (34.5 g), and the mixture was stirred at 1500 rpm for 120 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a first positive electrode material (1-2).
[0300] The volume ratio of the solid content to the liquid content of the obtained first positive electrode material (1-2) was 15:85. That is, the solid content concentration of the first positive electrode material (1-2) was 15% by volume.
[0301] [Preparation of the second powder material (2-1) for positive electrode]
[0302] Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 1 g of a conductive aid (ketjen black) and 80 g of a positive electrode active material (lithium iron phosphate) were stirred at 1500 rpm for 30 seconds to obtain a second positive electrode powder material (2-1).
[0303] The solid content concentration of the obtained second powder material for positive electrode (2-1) was 100 volume %.
[0304] [Preparation of support]
[0305] Support (S1): positive electrode current collector (aluminum foil, average thickness 20 μm, Ra 0.5 μm)
[0306] Support (S2): Two collector foils of 150 mm × 200 mm × 20 μm (thickness) are attached to a resin film (270 mm × 500 mm × 20 μm (thickness)) in such a way that the collector foils are separated by 40 mm from each other, the resin film portion between the collector foils is bent to the side opposite to the collector foil side, and the separated collector foils are bonded together without a gap (the surface Ra of the collector foil is 0.5 μm)
[0307] The Ra of the current collector mentioned above refers to the arithmetic mean roughness Ra of the surface on which the electrode material film is formed.
[0308] [Preparation of molded parts]
[0309] Scraper (B1): Stainless steel scraper
[0310] <Example 1>
[0311] The first material (1-1) for the positive electrode was applied onto the continuously conveyed support (S1) using a doctor blade to form a first film having a thickness of 100 μm.
[0312] Next, the second powder material (2-1) pressure-fed by a screw feeder manufactured by Kubota Corporation was applied onto the first film using an electromagnetic feeder, thereby forming a second film.
[0313] Then, if Figure 2 As in the example shown, the second film (second powder material) is leveled using a scraper (B1) capable of ultrasonic vibration.
[0314] Specifically, the scraper 40 was arranged so that the distance between the surface of the support 10 and the tip of the scraper 40 was 200 μm. In addition, the scraper 40 was connected to an ultrasonic oscillator and a phone of SEIDENSHA ELECTRONICS CO., LTD., so that ultrasonic vibration could be performed. Figure 2 As shown in FIG. 1 , the support 10 is transported and moved in the direction of arrow X, and the laminate of the first film 24 and the second film 34 formed on the support 10 is brought into contact with the scraper 40 performing ultrasonic vibration and is passed through the gap. By passing through the gap, the thickness of the laminate of the first film 24 and the second film 34 is limited so that the second film 34 with a thickness of 100 μm is formed on the first film 24 with a thickness of 100 μm. At this time, the amplitude of the vibration of the scraper performing ultrasonic vibration is 1 μm and the frequency is 35 kHz.
[0315] As described above, on the support 10, the electrode material film 50 of a single-layer structure is formed as a continuous film along the conveying direction (arrow X direction) of the support 10. The obtained electrode material film 50 has a film thickness of 200 μm.
[0316] Next, a vibration roller having a diameter of 100 mm and a turbine vibrator (UT322, EXEN Corporation) was first prepared. Figure 4 As shown, after the electrode material film 50 obtained in the above manner is placed on the support, the prepared vibration roller is pressed on the electrode material film 50 while vibrating, so that it moves relative to the surface of the support body 10, and the electrode material film 50 is pressurized and compressed. At this time, the vibration amplitude of the vibration roller is 10 μm and the frequency is 400 Hz.
[0317] The electrode material film 52 after being compressed by pressure had a film thickness of 190 μm and a solid content concentration of 65.5 vol %.
[0318] <Example 2>
[0319] The first material (1-2) for the positive electrode was applied onto the continuously conveyed support (S1) using a doctor blade to form a first film having a thickness of 80 μm.
[0320] Next, the second powder material (2-1) pressure-fed by a screw feeder manufactured by Kubota Corporation was applied onto the first film using an electromagnetic feeder, thereby forming a second film.
[0321] Then, if Figure 2As shown in the example, the second film (second powder material) was leveled using a scraper (B1) capable of ultrasonic vibration, as in Example 1. Specifically, the scraper 40 was arranged so that the distance between the surface of the support 10 and the front end of the scraper 40 was set to 200 μm. Figure 2 As shown in FIG. 1 , the support 10 is transported and moved in the direction of arrow X, and the laminate of the first film 24 and the second film 34 formed on the support 10 is brought into contact with the scraper 40 performing ultrasonic vibration and is passed through the gap. By passing through the gap, the thickness of the laminate of the first film 24 and the second film 34 is limited so that the second film 34 with a thickness of 120 μm is formed on the first film 24 with a thickness of 80 μm. At this time, the amplitude of the vibration of the scraper performing ultrasonic vibration is 1 μm and the frequency is 35 kHz.
[0322] Next, under the same conditions as in Example 1, the electrode material film 50 was pressed and compressed using a vibration roller.
[0323] The electrode material film 52 after being pressed and compressed had a film thickness of 190 μm and a solid content concentration of 65.5 vol %.
[0324] <Example 3>
[0325] After obtaining an electrode material film 50 having a film thickness of 200 μm by the same method as in Example 1, the electrode material film 50 was pressed and compressed by a roll press (SA-602 manufactured by TESTER SANGYO CO., LTD.) by the following method.
[0326] First, the roller press was configured so that the distance between the support surface and the outer periphery of the roller press was 190 μm. Then, the support was transported and moved so that the electrode material film 50 formed on the support came into contact with the roller press and passed through the gap at 10 mm / s to pressurize and compress the electrode material film 50.
[0327] The electrode material film 52 after being compressed by pressure had a film thickness of 190 μm and a solid content concentration of 65.5 vol %.
[0328] <Example 4>
[0329] After obtaining an electrode material film 50 having a film thickness of 200 μm by the same method as in Example 1, the electrode material film 50 was pressed and compressed by the following method using a scraper that vibrated ultrasonically.
[0330] First, an ultrasonic oscillator (DGS35-100-S, UC JAPAN CO., LTD.) and a frequency converter (C35-SD8, Uthe Japan CO., LTD.) were used to make a scraper that performs ultrasonic vibration. The scraper was configured so that the distance between the surface of the support and the front end of the scraper was 190 μm. The support was transported and moved so that the electrode material film 50 formed on the support came into contact with the scraper that performs ultrasonic vibration and passed through the gap. At this time, the amplitude of the vibration of the scraper that performs ultrasonic vibration was 1 μm and the frequency was 35 KHz.
[0331] The electrode material film 52 after being compressed by pressure had a film thickness of 190 μm and a solid content concentration of 65.5 vol %.
[0332] <Example 5>
[0333] After obtaining an electrode material film 50 having a film thickness of 200 μm by the same method as in Example 1, the electrode material film 50 was pressed and compressed by using a vibrating scraper in the following manner.
[0334] First, a PTFE resin film is placed on the electrode material film 50, and a scraper that performs ultrasonic vibrations as in Example 4 is brought into contact from above, and the electrode material film 50 is pressurized and compressed. Specifically, the scraper that performs ultrasonic vibrations is arranged in such a way that the distance between the surface of the support body and the front end of the scraper is set to 190 μm. In addition, the support body is transported and moved, so that the electrode material film 50 formed on the support body contacts the scraper that performs ultrasonic vibrations via the PTFE film, and passes through the gap. At this time, the amplitude of the vibration of the scraper that performs ultrasonic vibrations is 1 μm, and the frequency is 35 KHz.
[0335] As described above, on the support 10, the electrode material film 50 of a single-layer structure was formed as a continuous film along the conveying direction (arrow X direction) of the support 10. The obtained electrode material film 50 had a film thickness of 190 μm.
[0336] <Example 6>
[0337] The first material (1-1) for the positive electrode was applied to the collector foil of the support (S2) using a doctor blade to form a first film having a thickness of 100 μm. Next, the second powder material (2-1) was applied to the first film using an electromagnetic feeder and pressure-fed by a screw feeder manufactured by Kubota Corporation to form a second film.
[0338] Then, the resin film of the support (S2) was stretched to separate the two bonded collector foils. After the collector foils were separated, the shape of the laminate of the first film and the second film on the collector foil was observed using a CCD camera, and no damaged parts were observed.
[0339] Then, the second film (second powder material) formed on the first film of the collector foil was flattened using a scraper (B1) that vibrated ultrasonically in the same manner as in Example 1, and the thickness of the laminate of the first film and the second film was limited so that a second film with a thickness of 100 μm was formed on a first film with a thickness of 100 μm. Thus, an electrode material film with a continuous film and a single-layer structure was formed on each of the two collector foils.
[0340] Next, under the same conditions as in Example 1, the electrode material film was pressed and compressed using a vibration roller.
[0341] The thickness of the electrode material film after the pressurization and compression was 190 μm, and the solid content concentration was 65.5 vol %. In addition, no damage was observed in the electrode material film after the pressurization and compression.
[0342] <Evaluation>
[0343] (Evaluation of Non-uniformity of Solid Content Concentration in the In-plane Direction)
[0344] The thickness of the formed electrode material films was measured using a multi-color laser displacement meter manufactured by Keyence Corporation, and it was confirmed that they had the same thickness (here, an error of 5 μm or less was defined as “the same thickness”).
[0345] The electrode material film whose thickness was measured was punched out using a 2 cm square punching machine at 10 locations in the width and 10 locations in the length direction, for a total of 100 locations, to obtain 100 samples of 2 cm square.
[0346] Next, the masses of the 100 samples thus obtained were measured using an electronic balance.
[0347] The arithmetic mean value was calculated from the obtained measured values and used as the reference mass. The number of samples with a mass within 5% by mass relative to the reference mass was counted and evaluated with the number of samples counted. It can be said that the more samples counted, the less uneven the solid content concentration in the in-plane direction. The results are shown in Table 1.
[0348] The evaluation criteria are as follows.
[0349] -Evaluation Criteria-
[0350] A: The number of counted samples is 95 or more.
[0351] B: The number of counted samples is 90 or more and 94 or less.
[0352] C: The number of counted samples is 85 or more and 89 or less.
[0353] D: The number of counted samples was 84 or less.
[0354]
[0355] As described above, according to each of the examples, it was found that a sheet-shaped electrode molded body having a single-layer structure with a high solid content concentration and little unevenness in the solid content concentration in the in-plane direction was produced on a support.
[0356] Explanation of symbols
[0357] 10-support body, 20-imparting mechanism, 22-first material, 24-first film, 30-imparting mechanism, 32-second powder material, 34-second film, 40-scraper, 50-single-layer structure electrode material film, 52-pressurized single-layer structure electrode material film, 60-roller, 62-film, 70-pressure roller, 72-film, X-conveying direction of support body.
[0358] The invention of Japanese Patent Application No. 2022-120969 filed on July 28, 2022 is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical standard were specifically and individually described by reference.
Claims
1. A method for producing a sheet-shaped electrode molded body, comprising: In a first step, a first material including an electrode active material and an electrolyte solution is applied to a support to form a first film based on the first material; and In the second step, a second powder material containing an electrode active material and no liquid component is provided on the first film. Then, an electrode material film having a single-layer structure as a mixture of the first film and the second powder material is formed.
2. The method for producing a sheet-shaped electrode molded body according to claim 1, wherein: The second step is a step in which, after applying a second powder material containing an electrode active material and no liquid component to the first film, the second powder material applied to the first film is flattened by a molding member to limit the thickness of a laminate of the first film and the second powder material.
3. The method for producing a sheet-shaped electrode molded body according to claim 2, wherein: The forming part is a scraper or a roller.
4. The method for producing a sheet-shaped electrode molded body according to claim 2, wherein: In the second step, the second powder material applied onto the first film is leveled by a vibrating scraper or roller.
5. The method for producing a sheet-shaped electrode molded body according to claim 1, wherein: The second step is as follows: after imparting a second powder material containing an electrode active substance and not containing a liquid component to the first film, a thin film is placed on the second powder material imparted to the first film, and the second powder material is pressed from the thin film by a molding component, thereby flattening the second powder material imparted to the first film and limiting the thickness of the stack of the first film and the second powder material.
6. The method for producing a sheet-shaped electrode molded body according to claim 2 or 5, wherein: The method further includes a third step of compressing the stacked product with the restricted thickness by a vibrating pressurizing member after the second powder material applied to the first film is flattened in the second step to restrict the thickness of the stacked product of the first film and the second powder material.
7. The method for producing a sheet-shaped electrode molded body according to claim 1 or 2, wherein: The solid content concentration of the first material is 5 volume % to 48 volume %.
8. The method for producing a sheet-shaped electrode molded body according to claim 1 or 2, wherein: The thickness of the electrode material film of the single-layer structure is 50 μm to 250 μm, and the solid content concentration is 50 volume % to 80 volume %.
Citation Information
Patent Citations
Method for manufacturing lithium ion secondary battery
JP2017183079A
Method for manufacturing electrode for secondary battery
JP2018147807A
Floor slab cutting apparatus and floor slab cutting method
JP2022120969A